HADIS KONTEKSTUAL (Suatu Kritik Matan Hadis) (UINSI Samarinda, 2012)
This paper discusses the contextual tradition. Position as the explanatory tradition which al-Qur `an is a source of law for Muslims. As an explanation of al-Qur `an, the hadith of the Prophet would appear appropriate circumstances and background of the lives of the friends who are different, the instructions given by the Prophet any differently. Meanwhile, the friends also interpret the traditions of the Prophet in accordance with their respective capacities, so that the conclusions reached different results. Therefore it is necessary contextual understanding.